Clinical application of IUGA/ICS classification system for mesh erosion. Issue 5 (14th April 2015) - Batalden, Rebecca Posthuma; Weinstein, Milena M.; Foust‐Wright, Caroline; Alperin, Marianna; Wakamatsu, May M.; Pulliam, Samantha J.
Abstract : Aims: Our aim was to assess the usability of the IUGA/ICS classification system for mesh erosion in a tertiary clinical practice and to determine if assigned classification is associated with patient symptoms, treatment, and outcome. Methods: We retrospectively identified women who had mesh erosion after prolapse or incontinence surgery. Each erosion was classified using the IUGA/ICS category time site (CTS) system. Associations between classification and presenting symptom (asymptomatic, pain, bleeding, voiding, or defecatory dysfunction, infection, prolapse), treatment type, and outcome were evaluated with chi‐squared test, student's t ‐test, and univariate logistic regression. Results: We identified 74 subjects with mesh erosion; only 70% were classifiable. Asymptomatic patients (n = 19) (Category A) were more likely to be managed conservatively ( P  = 0.001). Symptomatic patients (n = 55) (Category B) were more likely to be managed surgically ( P  = 0.003). Other variables had no association with treatment. No variables were associated with outcome. Presenting symptom was associated with both treatment ( P  = 0.005) and outcome ( P  = 0.03). Asymptomatic subjects were more likely to have satisfactory outcome ( P  = 0.03). Urinary frequency and urgency were highly correlated with surgical management ( P  = 0.02). Conclusions: One third of mesh erosions could not be retrospectively coded using the IUGA/ICS classification. The components of the system were not predictive of treatment nor outcome with exception of the Category A (asymptomatic) and Category B (symptomatic). Asymptomatic women with mesh erosion can be successfully managed with conservative measures. Use of a classification system may be enhanced if the system is simplified by limiting the number of variables to those associated with interventions and patient outcome. Neurourol. Urodynam. 35:589–594, 2016 . © 2015 Wiley Periodicals, Inc.